PENGARUH PENGUNAAN PERASAN JERUK NIPIS (Citrus aurantifolia S.) TERHADAP MUTU ORGANOLEPTIK SATE DAGING KAMBING - Konuti, Rian; Ratulangi, F. S.; Rompis, J. E. G.; Rumondor, D. B. J. (ZOOTEC, 2018)
THE EFFECT OF LIME ((Citrus aurantifolia S.) JUICE LEVELS ON THE ORGANOLEPTIC QUALITY OF GOAT MEAT SATAY. The aim of this research is to know the effect of lime juice levels on the organoleptic quality of goat meat satay. Material used on this research were the whole thigh of goat (silver side part, outside part, outside flat part, eye round part) and limes. Randomized completely design (RCD) was used on this research with five treatments as follow: R0=600 gram dice cut meat (without lime), R1=600 gram dice cut meat (marinated in 5 mL lime juice for 30 minutes, R2=600 gram dice cut meat (marinated in 10 mL lime juice for 30 minutes, R3=600 gram dice cut meat (marinated in 15 mL lime juice for 30 minutes, and R4=600 gram dice cut meat (marinated in 20 mL lime juice for 30 minutes, and there were 35 repetitions (panelists) each treatment. Measurements taken were color, odor, taste, and tenderness of the goat meat satay. It was found on this research that, there were significant effects of treatment (lime juice) (P<0,05) on color, odor, tenderness, and taste of goat meat satay. It was concluded on this research that the preference level (Organoleptic quality) of lime juice on goat meat satay was 20 mL.Keywords: Goat meat, lime, satay, organoleptic quality